Cortical Inhibitory Imbalance in Functional Paralysis - Benussi, Alberto; Premi, Enrico; Cantoni, Valentina; Compostella, Silvia; Magni, Eugenio; Gilberti, Nicola; Vergani, Veronica; Delrio, Ilenia; Gamba, Massimo; Spezi, Raffaella; Costa, Angelo; Tinazzi, Michele; et al. (Frontiers in Human Neuroscience, 2020)
Background: Functional movement disorders, are characterized by neurological symptoms that have no identifiable pathology and little is known about their underlying pathophysiology. Objectives: To analyze motor cortex excitability and intracortical inhibitory and excitatory circuits’ imbalance in patients with flaccid functional weakness. Methods: Twenty-one consecutive patients with acute onset of flaccid functional weakness were recruited. Single and paired-pulse transcranial magnetic stimulation (TMS) protocols were used to analyze resting motor thresholds (RMT) and intracortical inhibitory (short interval intracortical inhibition - SICI) and excitatory (intracortical facilitation - ICF) circuits’ imbalance between the affected and non-affected motor cortices. Results: We observed a significant increase in RMT and SICI in the affected motor cortex (p<0.001), but not for ICF, compared to the contralateral unaffected side. Conclusions: This study extends current knowledge of functional weakness, arguing for a specific central nervous system abnormality which may be involved in symptoms’ pathophysiology.